Possibility of Using an Invasive Species Adenocaulon Adhaerescens Maxim. (Asteraceae) as a Medicin Plant - Vinogradova, Yulia; Shelepova, Olga; Vergun, Olena; Ganina, Anastasia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Many alien invasive species are characterized by the accumulation of biologically active substances antioxidants, which are used in the prevention of diseases of the cardiovascular system and many cancers. The purpose of this study was to compare the antioxidant (antiradical) properties of Adenocaulon adhaerescens Maxim extracts obtained from plants growing in both natural and secondary distribution ranges. The literature data on the analysis of medicinal properties of closely related species of the genus Adenocaulon are summarized. The antioxidant activity was determined by the method using 2,2-diphenyl-1-picrylhydrazil (DPPH) on spectrophotometer Genesis 20, the USA at the Slovak University of Agriculture in Nitra (Slovak Republic). Water and alcohol extracts (methanol and ethanol) were tested. The total antioxidant activity of extracts from leaves of juvenile plants was about 80 % (alcoholic extracts) and 34 % (water extracts). The total antioxidant activity of leaf extracts collected from flowering plants was 76 % (methanol extracts), 59 % (ethanol extracts), and 48 % (water extracts). The total antioxidant activity of extracts from inflorescences was significantly higher and amounted to 83 % (methanol extracts), 85 % (ethanol extracts), and 49 % (water extracts). Indicators of antioxidant activity of the aboveground part of plants collected in populations from the natural and secondary ranges do not have reliable differences. Methanol extracts from plants collected in the natural range have the antioxidant activity of 77–78 %, ethanol extracts of 78–81%, and water extracts of 61–66 %. In plants from invasive populations, the antioxidant activity of methanol extracts is 77–80 %, ethanol extracts 76–79 %, water extracts 32–67 %. The studied species demonstrated a significant antioxidant activity comparable to many valuable medicinal plants, such as Urtica dioica L., Bidens pilosa Linn., Acacia auriculiformis A. Cunn, Salvia officinalis L., and others. Thus, alien (A. adhaerescens) which has successfully adapted to the Moscow climate and formed a stable invasive population, may become a potential source of antioxidants to improve the system of antioxidant protection of humans.